Complex neurological interplay: adult-onset migraine-triggered seizures in schizencephaly—a case report - Wang, Yuzhu; Zhou, Fu; Liu, Fei; Wu, Xiaohui; Chen, Xuan; Xi, Zhiqin (Frontiers in Human Neuroscience, 2025)
Schizencephaly is a rare congenital cerebral malformation typically diagnosed in early childhood due to serious neurological manifestations. Our case report described a patient with open lip schizencephaly, notable for three unique aspects. First, the patient experienced epileptic seizures in adulthood, which is atypical compared to the usual onset in childhood. Additionally, the patient reported migraine-like pain occurring seconds before each epileptic seizure, with a short interval and regular occurrence. Finally, contrary to the expected severity of symptoms in a patient with open lip schizencephaly, the patient was able to live independently in daily activities, maintained normal cognitive function, and effectively managed both seizures and headaches with standard medication. The purpose of this report is to highlight the significant role of schizencephaly as a causative factor in adult-onset epilepsy and to emphasize the need for a comprehensive therapeutic approach addressing both the structural and functional aspects of this complex neurodevelopmental condition (under the premise of schizencephaly, there were migraine-like attacks in the short term before epileptic seizures).